Time in Ancient Greek Literature Studies in Ancient Greek Narrative, Volume 2 - de Jong, Irene J.F; Nünlist, René (Mnemosyne, Supplements, 2007)
This is the second volume of a new narratological history of Ancient Greek lietrature, which deals with aspects of time: the order in which events are narrated, the amount of time devoted to the naration, and the number of times they are presented.; Readership: All those interested in ancient Greek literature, narrative theory, literary history, comparative literature.